Distorsi Pasar Dalam Perspektif Ekonomi Islam - Rahma, Sri; Sintyasari, Novi; Anugrah, Rizki; Ariyadi, Ahmad; Muthma’Innah, Nawra Izzah (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
This method aims to find out about market distortion in the perspective of Islamic economics. Basically, Islamic economics requires a free market mechanism without any sign of intervention. Market distortion in the perspective of Islamic economics is understood as any form of deviation from the ideal market mechanism, resulting in imbalance and injustice in the economic transaction process. Market distortion is a form of deviation that causes imbalance and injustice in the market that must be avoided. This study aims to further explore the forms of distortion such as tadlis, gharar, maysir, ihtikar and bai'najasy and to recognize how they manifest in the transaction process in the Islamic capital market, especially the secondary market, so that the Islamic securities transaction process truly reflects Islamic economic transaction activities that have the values of brotherhood, common interests, morality, orientation to the world and the hereafter, no exploitation.